2020
DOI: 10.1038/s42003-020-01409-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial organization in microbial range expansion emerges from trophic dependencies and successful lineages

Abstract: Evidence suggests that bacterial community spatial organization affects their ecological function, yet details of the mechanisms that promote spatial patterns remain difficult to resolve experimentally. In contrast to bacterial communities in liquid cultures, surface-attached range expansion fosters genetic segregation of the growing population with preferential access to nutrients and reduced mechanical restrictions for cells at the expanding periphery. Here we elucidate how localized conditions in cross-feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 65 publications
(83 reference statements)
2
45
0
Order By: Relevance
“…Another example of an environmental effect involves two mutants of Pseudomonas stuzeri. Depending on the pH, the mutants can shift from competition to strong cross-feeding of nitrite, which is a toxic compound at low pH (Borer et al, 2020).…”
Section: Mechanisms Behind Cross-feedingmentioning
confidence: 99%
“…Another example of an environmental effect involves two mutants of Pseudomonas stuzeri. Depending on the pH, the mutants can shift from competition to strong cross-feeding of nitrite, which is a toxic compound at low pH (Borer et al, 2020).…”
Section: Mechanisms Behind Cross-feedingmentioning
confidence: 99%
“…Laboratory and in silico experiments demonstrated that stochastic processes [ 32 , 36 ] and mechanical forces acting between cells [ 42 , 43 ] in combination with initial spatial positioning [ 24 , 36 ] can control the dynamics of diversity loss during sessile microbial range expansion. Further investigations demonstrated the importance of initial spatial positioning when sustained by the local substrate landscape, thus leading to the establishment of successful lineages at the expansion edge [ 44 ]. In other words, the presence of a specific cell-type at the expansion edge may result from stochastic processes that do not require beneficial mutations.…”
Section: Introductionmentioning
confidence: 99%
“…This expectation, however, is not always realized. We analyzed patterns of spatial self-organization that emerged as a synthetic two-strain cross-feeding community expanded across an initial environment that was spatially homogeneous [ 18 , 20 , 37 ] (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%